Efficacy of Caspofungin Alone and in Combination with Voriconazole in a Guinea Pig Model of Invasive Aspergillosis - Kirkpatrick, William R. (American Society for Microbiology, 2002)
The antifungal activity of caspofungin acetate (CAS) alone and in combination with voriconazole (VRC) was evaluated in an immunosuppressed transiently neutropenic guinea pig model of invasive aspergillosis. Guinea pigs were immunosuppressed with triamcinolone at 20 mg/kg of body weight/day subcutaneously beginning 4 days prior to lethal intravenous challenge with Aspergillus fumigatus and were made temporarily neutropenic with cyclophosphamide administered at 150 mg/kg intraperitoneally (i.p.) 1 day prior to challenge. Therapy with i.p. CAS at 1 and 2.5 mg/kg/day (with and without oral VRC at 5 mg/kg/day), oral VRC at 5 mg/kg/day, or i.p. amphotericin B (AMB) at 1.25 mg/kg/day was begun 24 h after challenge and was continued for 5 days. Mortality occurred in 12 of 12 untreated controls, whereas mortality occurred in 4 of 12 and 6 of 12 guinea pigs treated with CAS at 1 and 2.5 mg/kg/day, respectively, and in 3 of 12 guinea pigs treated with AMB. No mortality occurred among animals treated with CAS at 1 mg/kg/day plus VRC at 5 mg/kg/day, CAS at 2.5 mg/kg/day plus VRC at 5 mg/kg/day, or VRC at 5 mg/kg/day alone. Both CAS regimens increased the survival times and reduced the colony counts in tissue compared with those for the controls. Treatment with VRC and AMB significantly reduced the colony counts in the tissues of selected animals compared with those in the tissues of the controls. Treatment with VRC and AMB also resulted in reductions in colony counts in tissues compared with those in the tissues of animals treated with CAS (the difference was not statistically significant) and improved the survival times but did not sterilize tissues. Combination therapies with CAS plus VRC at either dose reduced colony counts in tissues 1,000-fold over those for the controls and were the only regimens that significantly reduced the numbers of positive cultures. The combinations of CAS plus VRC were highly effective in this model and should be further evaluated for use against invasive aspergillosis.